Risk Factors of Breast Cancer based on Case-Control Study in Women of Child-Bearing Age (WEBA) at Gambiran Hospital Kediri - Nurita Nilasari Bunga Kharisma Arifiana Putri; Eko Sri Wulaningtyas (Journal of Ners and Midwifery, 2021)
Breast cancer is a type of cancer that starts in the breast tissue and spreads throughout the body. Every year more than 185,000 women are diagnosed with breast cancer. This incidence is increasing in developed countries (Kemenkes RI, 2015). In Indonesia, a high rate of breast cancer, especially in Kediri, makes breast cancer the number one position of cancer in women, followed by cervical cancer. Based on research by Harrianto et al. at Dr. Cipto Mangunkusumo Hospital in the Journal of Public Health 8 (2) (2013) 121-126, breast cancer risk factors include a family history of breast cancer patients (15.79%), early menarche (8.77%), nullipara (7.02 %), and long-term use of pills containing estrogen (42.11%). In addition, there are also incidences of breast cancer, namely late menopause, history of breastfeeding, and obesity. From the description above, the purpose of this study is to determine and analyze the risk factors for breast cancer based on a case-control analysis in women at Gambiran Hospital, Kediri. This study uses data collection sheets and field studies, then processed for hypothesis testing so that the objectives of this research can be carried out. This study indicates a significant relationship between the risk factors for a breast cancer history with a p-value of 0.0000 OR 9.837. For women who have families with cancer should be aware of the onset of breast cancer. If they have reached puberty, it is recommended for early detection (screening test) through breast self-examination (BSE), IVA method, and mammography testing.